The ghost of Lancelot Biggs - Bond, Nelson S., 1908-2006; Ferman, Harry, 1906-1973 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Ghost of Lancelot Biggs" by Nelson S. Bond is a science fiction tale written in the early 20th century. This narrative blends elements of adventure and the supernatural, revolving around the titular character, Lancelot Biggs, who, after sacrificing himself in space to save his crew, appears as a ghost to convey critical information to his surviving shipmates. The book presents an intriguing exploration of friendship, sacrifice, and the boundaries of life and death through a futuristic lens. In this story, the main character, Bert Donovan, along with Captain Hanson and his daughter Diane, grapples with the reality of losing their friend Lancelot Biggs during a space mission. After receiving inexplicable news from their corporation and being compelled to embark on a new mission to Jupiter, they experience haunting apparitions of Biggs, sparking a mix of fear and hope. As they navigate through these mysterious occurrences, they uncover that Biggs has not perished but has found a way to communicate with them from the surface of Jupiter, where he has discovered a valuable resource called polarium. The crew must race against time and the gravitational threat of Jupiter to rescue their friend, relying on Biggs' clever ingenuity and their teamwork to survive and succeed in their mission. (This is an automatically generated summary.)
Release date is 2024-07-12
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space ships -- Fiction